BELT AND ROAD INITIATIVE (BRI) AND CHINA’S INTERNATIONAL DEVELOPMENT COOPERATION IN LATIN AMERICA: BETWEEN ADHESIONS AND HESITATIONS - Ticiana Gabrielle Amaral Nunes; Carlos Renato da Fonseca Ungaretti Lopes Filho; Giulia Marianna Rodrigues Di Marco; Marco Aurélio Alves de Mendonça (Revista Tempo do Mundo, 2022)
The last decade has witnessed a substantial increase in the volume of Chinese financing for large-scale projects in developing countries. Although it cannot be said that these financing are strictly limited to the concept of “aid” in its conventional meaning, they are considered the cornerstone of China’s International Development Cooperation (IDC) and have thus constituted a valuable alternative for emerging economies. Following this premise, the article analyzes the expansion of flows in Latin America and the Caribbean (LAC), focusing on the increasing projection of the Belt and Road Initiative (BRI) in the region. As for the theoretical framework, the study employs literature review on IDC and South-South Cooperation (SSC) to examine the intrinsic characteristics of the Chinese model. Empirically, the research addresses the growth of Chinese banks financing in the region as well as the current framework of entrances and hesitations among the three largest regional economies (Brazil, Argentina and Mexico). It is argued that, although the Chinese cooperation dynamic does not match the conventional definition of the concept, it produces tangible effects on regional economies and their dependence vis-à-vis traditional donors which should not be overlooked.